On Initial Data of a Simple Conservative Scattering System That Can Be Transferred to Zero by a Sequence of Inputs from l ² - Nudel'man, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We describe the lineal of initial data of a simple conservative scattering system which can be transferred to zero by a sequence from l ². The proof is based on the known connection between the Lax - Phillips scattering theory and the theory of unitary operator nodes developed by B. Szokefalvi - Nagy, C. Foias, and M. S. Brodskii.